2012
DOI: 10.1016/j.hrthm.2012.04.034
|View full text |Cite
|
Sign up to set email alerts
|

The voltage-sensitive dye di-4-ANEPPS slows conduction velocity in isolated guinea pig hearts

Abstract: BACKGROUND Voltage-sensitive dyes are important tools for mapping electrical activity in the heart. However, little is known about the effects of voltage-sensitive dyes on cardiac electrophysiology. OBJECTIVE To test the hypothesis that the voltage-sensitive dye di-4-ANEPPS modulates cardiac impulse propagation. METHODS Electrical and optical mapping experiments were performed in isolated Langendorff perfused guinea pig hearts. The effect of di-4-ANEPPS on conduction velocity and anisotropy of propagation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…We measured conduction velocity transverse and longitudinal to the generalized fiber orientation for an S1 of 400 milliseconds, and during an S2 of 160 milliseconds. Conduction velocity was quantified with a previously validated algorithm that can distinguish between transverse and longitudinal conduction . In brief, this algorithm creates an isochrone map based on the activation times from the electrograms on the plaque.…”
Section: Methodsmentioning
confidence: 99%
“…We measured conduction velocity transverse and longitudinal to the generalized fiber orientation for an S1 of 400 milliseconds, and during an S2 of 160 milliseconds. Conduction velocity was quantified with a previously validated algorithm that can distinguish between transverse and longitudinal conduction . In brief, this algorithm creates an isochrone map based on the activation times from the electrograms on the plaque.…”
Section: Methodsmentioning
confidence: 99%
“…There is an evidence for influence of di-4-ANEPPS on cardiac impulse conduction through heart ventricles as well as 1167 A V node in various animal models. Slowing of the conduction velocity in longitudinal as well as transversal direction was described in isolated guinea pig heart [4]. In rat heart, influence of the di-4-ANEPPS on conduction through A V node as well as conduction through the ventricles was observed.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, the exact mechanisms of influencing cardiac impulse generation or its spreading through the heart tissue in the presence of di-4-ANEPPS are still not known. The slowing of cardiac impulse propagation in isolated guinea pig heart under di-4-ANEPPS was described by Larsen et al [4]. PQ interval prolongation and transient block of atrioventricular conduction in rat heart were reported by Nygren et al [5].…”
Section: Introductionmentioning
confidence: 84%
“…In addition, this method eliminates the need for voltage‐sensitive dyes and electromechanical uncouplers or other methods to reduce the contraction of the heart as required for optical mapping techniques. Di‐4‐ANEPPS, a commonly used dye in optical mapping studies, has been shown to alter cardiac electrophysiology, including prolongation of the PQ interval and QRS duration, and reduction of conduction velocity (Nygren et al 2003; Larsen et al 2010, 2012). Likewise, excitation–contraction uncouplers, such as 2,3‐butanedione monoxime, cytochalasin D and diacetyl monoxime, frequently used for optical mapping have been shown to have effects on action potential duration, conduction velocity, electrical restitution curve, calcium transient and ventricular fibrillation activation patterns (Qin et al 2003; Baker et al 2004; Cheng et al 2004; Kettlewell et al 2004).…”
Section: Discussionmentioning
confidence: 99%